191k views
2 votes
The equation of circle having a diameter with endpoints (-2, 1) and (6, 7) is

(x - 4)² + (y - 3)² = 25
(x - 2)² + (y - 4)² = 25
(x - 2)² + (y - 4)² = 100

User Glessard
by
4.9k points

1 Answer

2 votes

Answer:


(x-2)^(2)+(y-4)^(2)=25

Explanation:

step 1

Find the diameter of the circle

the formula to calculate the distance between two points is equal to


d=\sqrt{(y2-y1)^(2)+(x2-x1)^(2)}


A(-2,1)\\B(6,7)

substitute the values


d=\sqrt{(7-1)^(2)+(6+2)^(2)}


d=\sqrt{(6)^(2)+(8)^(2)}


d=√(100)


d=10\ units

The radius is half the diameter

so


r=10/2=5\ units

step 2

Find the center of the circle

the center of the circle is the midpoint between the endpoints of the diameter

so

The center is


((-2+6)/(2),(1+7)/(2))


(2,4)

step 3

Find the equation of the circle

The equation of the circle is


(x-h)^(2)+(y-k)^(2)=r^(2)

substitute the values


(x-2)^(2)+(y-4)^(2)=5^(2)


(x-2)^(2)+(y-4)^(2)=25

User Vedant Terkar
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.